d-6.3=-11

Simple and best practice solution for d-6.3=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for d-6.3=-11 equation:



d-6.3=-11
We move all terms to the left:
d-6.3-(-11)=0
We add all the numbers together, and all the variables
d+4.7=0
We move all terms containing d to the left, all other terms to the right
d=-4.7

See similar equations:

| 120+90+40+x=180 | | 3xx-8+10x=67 | | 14x-(4.5x+1615)=0 | | 3x(x-8)+10x=67 | | 2.6=2j | | 3x-20,5=6,5 | | 2u=15 | | 13-a=15-8 | | 1.5x^2-5x+10.5=0 | | v-42/8=7 | | 10s-14=0 | | 3/4=t/10 | | (4,5);m=6 | | 4r+12/8=4r-8/4 | | 2x+2x+(-6)=-14 | | (5x+5)+(7x-19)=180 | | 2(u-62)=40 | | b-5=15-6 | | (3x5)=2 | | (5x+5)-(7x-19)=180 | | 4/5=n+9/35 | | 4x+(-3)=17 | | 19b-11=17b+13 | | 7=h-5/8 | | 3=2x=5 | | -4.4-5x=13.6 | | 62=2(b+12) | | 6x=3=21 | | 11-2h=1 | | 5425=(15500)(8.75)(t) | | 12-4=c-5 | | 25(4x)=6x^2+4x |

Equations solver categories